Tackling Ischemic Reperfusion Injury With the Aid of Stem Cells and Tissue Engineering - Zamorano, Mauricio; Castillo, Rodrigo L.; Beltran, Jorge F.; Herrera, Lisandra; Farias, Joaquín A.; Antileo, Christian; Aguilar-Gallardo, Cristobal; Pessoa, Adalberto; Calle, Yolanda; Farias, Jorge G. (Frontiers in Physiology, 2021)
Ischemia is a severe condition, in which blood supply (and thus oxygen) to organs/tissues is interrupted/reduced. This is usually due to a clog or blockage in the arteries that feed the affected organ. Reinstatement of blood flow is essential to salvage ischemic tissues, restoring oxygen, and nutrient supply. However, reperfusion itself does not come disburdened. Ischemia-reperfusion injury is often prompted by the local and systemic inflammatory reaction, as well as oxidative stress, and contributes to the organ and tissue-damage. In addition, the duration, and consecutive ischemia-ischemia reperfusion cycles, are related with the severity of the damage, and could lead to chronic wounds. Clinical pathophysiological conditions associated to reperfusion event, include stroke, myocardial infarction, wounds, lung, renal, liver, and intestinal damage/failure, which in due process are concomitant with disability, morbidity, and mortality. Consequently, preventive or palliative therapies for this injury are on demand. Tissue engineering offers a promising toolset to tackle with ischemia reperfusion injuries. By harnessing the benefits of stem cells (i.e., self-renewal, differentiability, anti-inflammatory, and immunosuppressants effects), functional biomaterials, and bioprocess design; to produce cell therapeutics capable of this objective; or producing tissue mimics, and physiological environments, as a platform of study to provide a better-understanding of the reperfusion condition, as well as to assess the effect of drugs. This review article, presents a synopsis, and discusses tissue engineering applications available to treat various types of ischemia-reperfusion, ultimately aiming to highlight possible therapies, and to bring closer the gap between preclinical, and clinical settings.